SARS-CoV-2 Variants and Vaccines: Pledge to global response! - Roy, Sushmita; Mahtab Uddin, Bhuiyan Mohammad; Ahmed, Iftikhar (Bangladesh Journal of Medical Microbiology, 2021)
The detection of SARS-CoV-2 variants correlates to the rapid increase in the number of COVID-19 cases. The variants may emerge with fatal consequences to the usual resistance to the immunity arbitrated by the available vaccines to prevent the pandemic of COVID-19. When some variants of interest have increased transmissibility or virulence, the priority of appropriate public health measures and vaccination programs will increase. Still and all, the genomic surveillance must continue to monitor this trend as these observations have grave implications for mitigation and vaccination policies and must be considered by policy makers when designing public health interventions. Moreover, the global response must be directed toward urgency with scientific reliability. Bangladesh J Med Microbiol 2021; 15 (2): 30-35